Who needs the social model of disability? - Adam, Sofia; Koutsoklenis, Athanasios (Frontiers in Sociology, 2023)
Over the past two decades, there has been a growing shift away from the Social Model of Disability (SMD) in both theory and practice. This article aims to substantiate the relevance of SMD by addressing the main arguments against it and by identifying why and for whom it is still relevant. In the introductory section, we focus on the recent production of multiple disability models in order to contextualize their emergence and elucidate the reasons behind their proliferation. In the main section of the article, we critically engage with three lines of criticism against SMD in order to explain why it remains relevant and for whom. Our main point is that, in the context of the neoliberal capitalist era, the SMD is indispensable for all disabled persons who have been denied their dignity, both in material and cultural terms.